Figure Of Speech In Fiction And Studying The Concept Of Ellipsis - Nasretdinova, Mukhlisa Nizometdinovna (PT. Batari Edu Calya, 2023)
This article examined different approaches to determining the meaning of the ellipse and elliptical structures and analyzed ellipsis as a transformation of a stylistic device in the works of Ernest Hemingway when translated into Russian.